2014
DOI: 10.1183/09031936.00152413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of airflow obstruction in  317 000 never-smokers in China

Abstract: In China, the burden of chronic obstructive disease (COPD) is high in never-smokers but little is known about its causes in this group.We analysed data on 287 000 female and 30 000 male never-smokers aged 30–79 years from 10 regions in China, who participated in the China Kadoorie Biobank baseline survey (2004–2008). Prevalence of airflow obstruction (AFO) (pre-bronchodilator forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) <0.7 and below the lower limit of normal (LLN)) was estimated, by age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
51
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 28 publications
4
51
0
1
Order By: Relevance
“…Without doubt, the report by SMITH et al [7] is a convincing, valuable addition to the current evidence, even if it challenges the traditional view of burning of biomass as an ''established'' risk factor for chronic respiratory disease, including COPD. These results should be replicated by other (ideally) longitudinal studies and the implications for public health policy to reduce household air pollution should be perhaps revisited in the light of consistent, comparable and convincing evidence.…”
mentioning
confidence: 95%
See 2 more Smart Citations
“…Without doubt, the report by SMITH et al [7] is a convincing, valuable addition to the current evidence, even if it challenges the traditional view of burning of biomass as an ''established'' risk factor for chronic respiratory disease, including COPD. These results should be replicated by other (ideally) longitudinal studies and the implications for public health policy to reduce household air pollution should be perhaps revisited in the light of consistent, comparable and convincing evidence.…”
mentioning
confidence: 95%
“…SMITH et al [7] found significant, independent associations of CAO with reported history of tuberculosis and also with low household income. Given that pulmonary tuberculosis has a well-defined natural history, distinct from tobacco smoking-related COPD, these associations should be regarded as complications of healed pulmonary tuberculosis and should be considered as a differential diagnosis of COPD in nonsmoking adults, until a better understanding of causal links can be established through cohort studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is treated as such, leading to biases in research and clinical medicine. The bias arising from the use of 80% predicted as a cut-off leads to over-estimation of the severity of respiratory impairment and its prevalence rate; it has undoubtedly also affected the otherwise excellent study of SMITH et al [1].…”
mentioning
confidence: 99%
“…First, most COPD research in the developed world has focused on current and former smokers. Growing literature has examined COPD in never-smokers, particularly in the developing world [6]. The factors that predict COPD development and progression in smokers may differ from those in never-smokers.…”
mentioning
confidence: 99%